P–199 A case report to suggest that there must be other mutations than PATL2 or TUBB8 to cause oocyte maturation arrest. (6th August 2021) - Molinari, E; Yang, M; Hu, J; Zhang, L; Albertini, D F; Barad, D H; Gleicher, N
Abstract: Study question: What causes our patient's repeated almost complete oocyte maturation arrest (OMA)? Summary answer: Since we did not detect PATL2 and TUBB8 mutations, both known to cause OMA, this case was likely caused by mutations in HUS1 and ITGB3 What is known already: OMA has been associated with loss-of-function in key genes, such as PATL2 and TUBB8. Such patients have, however, uniformly have been unable to conceive with IVF Study design, size, duration: We here report the case of repeatedly presenting patient between 2009 until 2020 (age 30 at 1st and 41 at last visit). Participants/materials, setting, methods: The couple underwent 7 IVF treatments under several ovarian stimulation protocols at different gonadotropin dosages and in different preparations to try to recruit mature eggs. She conceived in her 2nd IVF cycle in 2009 and delivered uneventfully in 2010. She then conceived spontaneously and delivered a healthy boy in 2014. The couple since then has been attempting another pregnancy. Remarkably, in all IVF cycles all eggs but one arrested at prophase. Main results and the role of chance: The female demonstrates abnormally high ovarian reserve for age (AMH=5.9 ng/mL in 2019) (mean, 10.6 oocytes). In all cycles, all but one retrieved were immature. In vitro maturation rate for the GV oocytes was 28%. Resultant M2s, however, demonstrated morphological abnormalities, such as giant polar bodies. In vivo M2s, in contrast, were always morphologically unremarkable, and their fertilization rate was 85%. Embryo morphology deteriorated appreciatively with advancing age. Sanger sequencing for TUBB8 and PATL2 genes were unremarkable. Whole genome sequencing of her and her sister (who had no fertility problems) revealed mutations of genes belonging to the integrin family (ITGB3) and DNA repair checkpoint (HUS1), both of which could be determinants in the observed maturation arrest. Limitations, reasons for caution: A functional study, coupled with imaging of the discarded material, will likely offer further information regarding the mechanisms leading to OMA in this female. Wider implications of the findings: This case report represents a new phenotype of female infertility, characterized by almost complete maturation arrest which, however, still offers opportunity for pregnancy. Further isolation of underlying mutation(s) may offer additional insights about checkpoints required for the transition of prophase to metaphase in human oocytes. Trial registration number: NA